1 - Wasted Citizenship? Reclaimers and the Privatised Expansion of the Public Sphere: https://doi.org/10.4314/ad.v34i3-4.63525 - Samson, Melanie (Africa Development, 2009)
A large body of literature explores changes in the public sphere related to the transfer of services and activities performed by the public into the private sector. Less attention has been paid, however, to the privatised expansion of the public sphere. This article explores such a process in Metsimaholo, South Africa, where the municipality sought to bring landfill recycling into the realm of public policy through a public-private partnership. As informal reclaimers had salvaged recyclables at the dump for several decades, this contract amounted to an enclosure of the waste commons which dispossessed them of control over their livelihood and confined them to the informal economy. Countering structuralist accounts of accumulation by dispossession and top-down approaches to governmentality, the article focuses on how reclaimers contested these processes. It argues that before the reclaimers could negotiate with the state, they needed to mount an ‘ontological insurrection’ to counter their dismissal as mere ‘detritus’ and demand that the conception of the public sphere be expanded to include them as legitimate actors in the realm of public policy. While this may result in a reconfiguration of the public sphere, it is unclear whether it would challenge the current privatised nature of its expansion.